2021
DOI: 10.1016/j.nmd.2021.07.299
|View full text |Cite
|
Sign up to set email alerts
|

Sma - Treatment

Abstract: Neuromuscular Disorders 31 (2021) S47-S162 treatment was ongoing in 7/13 patients. As of November 12, 2020, 31 patients (IV cohort, n = 23; IT cohort, n = 8) were enrolled in LT-002. One patient in each cohort reported SAEs, and one AESI was reported in the IV cohort (treatment-unrelated). None required permanent ventilation and 9 patients reported baseline respiratory support. Among patients for whom motor milestone data are available from baseline visits as of the data cutoff, 11 new milestones that were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Similar primary endpoint results were seen in the patients with two SMN2 copies, with 14/14 of these patients (100%) achieving independent sitting at any visit up to 18 months of age (90). However, while 93% of patients with three SMN2 copies achieved independent standing within the World Health Organization (WHO) developmental window (87), this endpoint was achieved by 50% of patients with two SMN2 copies (90), and the median time to independent walking was 422 days in those with three copies vs. 493 days in those with two copies (87, 90). All 15 of the patients with three SMN2 copies treated with onasemnogene abeparvovec were alive and free from permanent ventilation at the end of the study (87).…”
Section: Onasemnogene Abeparvovecsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar primary endpoint results were seen in the patients with two SMN2 copies, with 14/14 of these patients (100%) achieving independent sitting at any visit up to 18 months of age (90). However, while 93% of patients with three SMN2 copies achieved independent standing within the World Health Organization (WHO) developmental window (87), this endpoint was achieved by 50% of patients with two SMN2 copies (90), and the median time to independent walking was 422 days in those with three copies vs. 493 days in those with two copies (87, 90). All 15 of the patients with three SMN2 copies treated with onasemnogene abeparvovec were alive and free from permanent ventilation at the end of the study (87).…”
Section: Onasemnogene Abeparvovecsupporting
confidence: 69%
“…Strauss and colleagues reported a subgroup analysis from the phase 3 SPR1NT study in presymptomatic infants at risk of developing SMA who had three SMN2 copies (n = 15) (87). They did not directly compare outcomes in treated patients with three vs. two SMN2 copies, because the primary study endpoint was different between groups (independent sitting at any visit up to 18 months of age in those with two SMN2 copies vs. independent standing within 24 months of age in those with three SMN2 copies) (90). All 15 infants with three SMN2 copies achieved the primary endpoint (independent standing for ≥3 s at any visit up to 24 months of age); the median time to this milestone was 377 days, and 14/15 (93%) achieved independent standing within the normal developmental window, compared with 24% in the Pediatric Neuromuscular Clinical Research (PNCR) natural history study (p < 0.0001).…”
Section: Onasemnogene Abeparvovecmentioning
confidence: 99%
“…The key clinical manifestations include muscle weakness, atrophy, and hypotonia. Patients with SMA may also exhibit respiratory difficulties, joint contractures, and scoliosis (42). It is essential to recognize these clinical signs early, as timely intervention can significantly impact the prognosis and quality of life for affected individuals.…”
Section: Molecular Mechanisms Of Smamentioning
confidence: 99%
“…In the STR1VE study, 20 out of 22 patients were free of permanent ventilation at the age of 14 months, while in the START study all patients in the therapeutic-dose cohort were free of permanent ventilation at the age of 24 months, in striking contrast with natural history studies. Initiating treatment in presymptomatic patients has demonstrated the potential to yield a more favorable prognosis of both motor development and respiratory function (92). Real-world and extension studies evidence showed favorable respiratory outcomes (93)(94)(95)(96)(97).…”
Section: Novel Sma Treatments and Their Impact On Sleep And Respirato...mentioning
confidence: 99%